Sargassum fusiforme fucoidan modifies gut microbiota and intestinal metabolites during alleviation of hyperglycemia in type 2 diabetic mice. Issue 8 (30th March 2021) - Wu, Qifang; Wu, Siya; Cheng, Yang; Zhang, Zhongshan; Mao, Genxiang; Li, Shijun; Yang, Yue; Zhang, Xu; Wu, Mingjiang; Tong, Haibin
Abstract : Sargassum fusiforme fucoidan (SFF) modifies gut microbiota and intestinal metabolites of HFD/STZ-induced type 2 diabetic mice during alleviation of diabetic symptoms, thus implying the benefits of SFF as an adjuvant agent for T2DM. Abstract : Type 2 diabetic mellitus (T2DM) is a complicated metabolic disorder that is now considered as a major global public health problem. Fucoidan exhibits diverse biological activities, especially prevention of metabolic diseases. In this regard, we herein aimed to reveal the beneficial effect of Sargassum fusiforme fucoidan (SFF) on high-fat diet (HFD) and streptozotocin (STZ) induced T2DM mice. We noted that on the one hand, SFF significantly decreased fasting blood glucose, diet and water intake, and hyperlipidemia, while on the other hand, it improved glucose tolerance. Furthermore, SFF reduced epididymal fat deposition, attenuated the pathological changes in heart and liver tissues, and decreased oxidative stress in diabetic mice. To explore the underlying mechanisms of these ameliorative effects, the gut microbiota was analyzed. Notably, SFF highly enriched benign microbes including Bacteroides, Faecalibacterium and Blautia, as well as increased levels of (R)-carnitine and choline in the colon of diabetic mice. This may be a potential mechanism for alleviating T2DM, thus implying the benefits of SFF as an adjuvant agent for T2DM treatment. Taken together, this study demonstrated a promising application of fucoidan as one of the adjuvant agents for the management of T2DM in the future.